Retrospective analysis of experience of treatment of complex choledocholithiasis - V. V. Grubnik; B. V. Evsikov; D. V. Gerasimov (Клінічна хірургія, 2022)
Objective. Estimation of the clinical results application, concerning various methods of the complex choledocholithiasis treatment.